2014
DOI: 10.1093/tropej/fmu017
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with Amikacin or Piperacillin-Tazobactum Empirically in Neonates at Risk for Early-Onset Sepsis: A Randomized Controlled Trial

Abstract: Monotherapy with amikacin as an empirical antibiotic did not result in a higher incidence of treatment failure in neonates at risk for early-onset sepsis as compared with piperacillin-tazobactum. Both antibiotics were effective in management of babies with early-onset sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The longest treatment duration for suspected EOS reported in this compilation was ≥7 days [3] and the shortest was 3 days or less [3,57]. Two studies did not mention clearly the treatment duration used in their study [26,54].…”
Section: Treatment Duration With Antibiotics For Eosmentioning
confidence: 90%
See 4 more Smart Citations
“…The longest treatment duration for suspected EOS reported in this compilation was ≥7 days [3] and the shortest was 3 days or less [3,57]. Two studies did not mention clearly the treatment duration used in their study [26,54].…”
Section: Treatment Duration With Antibiotics For Eosmentioning
confidence: 90%
“…All articles were published between the year 2003 and 2016 with three RCTs, two prospective, and six retrospective studies. The largest sample population was 128,914 babies reported in a retrospective study by Clark et al [25] and the smallest sample population was 59 babies reported in a RCT study by Tewari and Jain [54].…”
Section: Evidence-based Compilationmentioning
confidence: 96%
See 3 more Smart Citations